Isolasi, Identifikasi Dan Uji Antibakteri Senyawa Triterpenoid Dari Ekstrak n-Heksana Daun Tempuyung (Sonchus arvensis L.) - Rumondang, Meutia (Chem Info Journal, 2013)
Isolation, identification, and antibactery test of triterpenoid compounds from n-hexane extract of tempuyung leaves (Sonchus arvensis L.) has been done. Maceration from 700 gram of dried leaves powder tempuyung with ethanol and then was partitioned by liquid-liquid extraction with n-hexane condensed n-hexane extracts was 4 gram. Phytochemical test result using Liebermann-Burchard showed that the n-hexane extract contained positive triterpenoid. Separation of n-hexane extract by column chromatography generated positive isolates of triterpenoid in E fraction and obtained triterpenoid isolates as 0.406 grams. Identification results of triterpenoid isolates from FT-IR spectrophotometer showed C=O ester, -CH3, -CH2, and C-O ester functional groups whereas identification results from GC-MS showed triterpenoid with molecular mass 552 g/mol and was suspected as pentacyclic triterpenoid ester. Antibactery test results showed MIC values of 50 ppm for ethanol extract, n-hexane extract, E fraction and triterpenoid isolates against E. coli and S.aureus.